Update of the PANCCO clinical practice guidelines for the treatment of ulcerative colitis in the adult population - Juliao Baños, F.; Grillo Ardila, C. F.; Alfaro, I.; Andara Ramírez, M. T.; Avelar Escobar, O.; Barahona Garrido, J.; Bautista Martínez, S.; Bosques Padilla, Francisco Javier; De Paula, J. A.; Ernest Suárez, K.; Galiano, M.T.; Iade Vergara, B.; et al. (Asociación Mexicana de Gastroenterología, 2022)
Ulcerative colitis (US) is a chronic disease of unknown etiology. It is incurable and its clinical course is intermittent, characterized by periods of remission and relapse. The prevalence and incidence of the disease has been increasing worldwide. The update presented herein includes the participation of healthcare professionals, decision-makers, and a representative of the patients, all of whom declared their conflicts of interest. Answerable clinical questions were formulated, and the outcomes were graded. The information search was conducted on the Medline/PubMed, Embase, Epistemonikos, and LILACS databases, and covered grey literature sources, as well. The search was updated on November 30, 2020, with no restrictions regarding date or language. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) classification system was implemented to establish the strength of the recommendation and quality of evidence. A formal consensus was developed, based on the RAND/UCLA methodology and the document was peer reviewed. The short version of the clinical practice guidelines for the treatment of ulcerative colitis in the adult population is presented herein, together with the supporting evidence and respective recommendations. In mild-to-moderate UC, budesonide MMX is an option when treatment with 5-ASA fails, and before using systemic steroids. In moderate-to-severe UC, infliximab, adalimumab, vedolizumab, ustekinumab, and tofacitinib can be used as first-line therapy. If there is anti-TNF therapy failure, ustekinumab and tofacitinib provide the best results. In patients with antibiotic-refractory pouchitis, anti-TNFs are the treatment of choice.